Rural life in eighteenth-century English poetry - Goodridge, John, 1953- (Cambridge studies in eighteenth-century English literature and thought, 1995)
Recent research into a self-taught tradition of English rural poetry has begun to offer a radically new dimension to our view of the role of poetry in the literary culture of the eighteenth century. In this important new study John Goodridge offers a detailed reading of key rural poems of the period, examines the ways in which eighteenth-century poets adapted Virgilian Georgic models, and reveals an illuminating link between rural poetry and agricultural and folkloric developments. Goodridge compares poetic accounts of rural labour by James Thomson, Stephen Duck, and Mary Collier, and makes a close analysis of one of the largely forgotten didactic epics of the eighteenth century, John Dyer's The Fleece. Through an exploration of the purpose of rural poetry and how it relates to the real world, Goodridge breaks through the often brittle surface of eighteenth-century poetry, to show how it reflects the ideologies and realities of contemporary life.